Influence of perceived value on satisfaction and continuance usage intention: e-hailing services - Yapp, Emily Hon Tshin; Jasmine A. L. Yeap (European Publisher, 2020)
Customer loyalty is always an agenda that organisations would like to achieve. However, it is not an easy agenda to be achieved. This is not an exceptional agenda for collaborative consumption services particularly in e-hailing services. Therefore, to ensure customer loyalty particularly in continuance usage intention, e-hailing organisations need to focus on users’ perceived value because literature states that perceived value influences users’ satisfaction, and this will lead to customer loyalty. The Partial Least Squares (SmartPLS version 3.2.8) analysis revealed that the customer perceived value which consists of economic value, convenience value, sustainability value and hedonic value positively influence users’ satisfaction and subsequently, users’ satisfaction positively influence users’ continuance usage intention. As a result, e-hailing organisations need to improve and concentrate on their services especially those related to providing economic value, convenience value, sustainability value and hedonic value. Managerial implications as well as the future research directions are duly discussed.